Sosialisasi Seminar Kepenulisan Karya Ilmiah untuk Mengembangkan Kreativitas dan Inovasi Siswa MAN 1 Malang - Ardiansyah, Ahmad Irfan; Putri, Wahyu Endah Adhella (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Writing scientific papers is an essential academic activity for the development of creativity and innovation, in addition to being something that students will encounter both at high school and college levels. However, it was found that many students still do not have a comprehensive understanding of scientific papers and their components. To overcome this, the Teaching Assistance students of Malang State University on Wednesday, May 8, 2024 held a socialization in the form of a scientific paper seminar held in Hall 1 MAN 1 Malang which was attended by teachers and representatives of classes X and XI as participants with the aim of improving students' understanding of the structure, methods, and types of scientific papers. The implementation of this activity consists of the stages of planning, implementation, and evaluation. The implementation of this seminar activity shows that students have a better understanding of the concepts, structures, and techniques for compiling scientific papers. The success of the implementation of this scientific paper seminar activity cannot be separated from the cooperation and collaboration between students, teachers, and students so that students as the target audience can accept and understand better about writing scientific papers.